Which STEM careers are most appealing? Examining high school students' preferences and motivational beliefs for different STEM career choices - Emily Q. Rosenzweig; Xiao-Yin Chen (SpringerOpen, 2023)
Abstract Background Decades of research have examined what motivates students to pursue careers in science, technology, engineering, and mathematics (STEM) fields, but STEM careers are a broad category encompassing hundreds of distinct vocations. The present study examined high school students' relative preferences for pursuing some types of STEM careers over others and explored what motivational beliefs (defined in accordance with situated expectancy value theory) most influenced students' relative career preferences. A secondary goal was to examine whether there were differences in any patterns as a function of students' intersecting gender and racial/ethnic identities. A large sample of high school students (N = 526) completed an online survey during class time about their beliefs regarding fifteen different STEM career categories. Results Students' career preferences could be classified into four groups: appealing, unappealing, polarizing, or overlooked. The last category was the most common. Students primarily selected reasons related to utility and attainment value in influencing their choices of most- and least-preferred careers. However, within this category, beliefs about helping others were stronger influences on choosing most-preferred careers, whereas concerns about fitting in were more influential for choosing least-preferred careers. Gender and racial/ethnic comparisons suggest differentiation in how students think about the appeal of various career paths as early as high school. Implications Findings shed light on how students come to perceive some STEM career paths as relatively more appealing than others, with attention to gender and racial/ethnic differences in these processes. Findings also point to specific and actionable ideas for how teachers, counselors, and administrators can target career education to cultivate students' interest in STEM career paths, where there are particular needs.